The community table : effective fundraising through events - Urano, Susan Cole (Swallow Press/Ohio University Press, 2018)
"In The Community Table, Susan Urano translates her nonprofit's experience with a large-scale annual fundraiser into a step-by-step guide for organizers. Using real-life examples, she illustrates methods of team building, conflict resolution, and problem solving. Includes sample timelines, budgets, publicity plans, and committee structures."--Www.ohioswallow.com